Six development paths in Southeast Asia: Three plus three - Manuel F. Montes (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Six Southeast Asian countries (Cambodia, Lao People's Democratic Republic, Malaysia, Myanmar, the Philippines, and Thailand) defied Gunnar Myrdal's pessimistic prognosis in his 1968 volume, Asian Drama, regarding their prospects for development. In the past half-century, these countries raised agricultural productivity faster than population growth and displayed sufficient state capability to direct change towards a respectable level of industrial development. In this period, the contrasts in achievements among the six countries can be understood from the variations in their initial conditions, socio-political contexts, international relations, and economic policies. These contrasts are investigated across four areas: agriculture, industry, foreign trade and investment, and social development. By using a more socially grounded analytical approach à la Myrdal, it is possible to understand how unorthodox economic policies have been effective in overcoming developmental disadvantages. However, shortfalls in social development could make further progress difficult in the future.
Keywords: O13; O14; O15; O19; 330; agricultural reform; development; foreign investment; industrial policy; inequality; poverty reduction; soft state; trade